REPRESENTASI SIMBOLIK SISWA DALAM MENYELESAIKAN SOAL HOTS MATERI RELASI DAN FUNGSI KELAS VIII SMP - Ira Royana; Muhammad Win Afgani; Ambasari Kusuma Wardhani (Lentera Sriwijaya : Jurnal Ilmiah Pendidikan Matematika, 2021)
AbstractThis study aims to describe the symbolic representation of students in solving HOTS questions on the relation material and functions of class VIII SMP. Qualitative descriptive research method with case research form. The research subjects consisted of six grade VIII students of SMP N 22 Palembang, namely two high-ability students, two medium-ability students and two low-ability students. The data was collected by providing test questions, interviews and documentation. The results of data analysis show that high-ability students have errors in the function symbols, function equations, curly braces, and in determining the results. Students with abilities have several errors that cannot function, are incomplete in brackets, errors in curly braces, there are unacceptable problems and errors in the same symbol as low-ability students there are errors in the function symbol, complete in brackets  not curly braces on the set as well as errors in completion.Keywords: Representation, Ability, Error, symbol, Equation